Synergistic toxicity of 2,4-dichlorophenoxyacetic acid and arsenic alters biomarkers in rats - Demirel, Hasan Huseyin; Zemheri Navruz, Fahriye; Kucukkurt, Ismail; Arslan-Acaroz, Damla; Tureyen, Ali; Ince, Sinan; Navruz, Fahriye Zemheri (Oxford Univ Press, 2023)
2,4-dichlorophenoxyacetic acid (2,4-D) and arsenic cause severe and extensive biological toxicity in organisms. However, their interactions and toxic mechanisms in co-exposure remain to be fully elucidated. In this study, 28 four-week-old female rats were divided into four groups and exposed to 100 mg/L arsenic or/and 600 mg/L 2,4-D through drinking water for a period of 28 days. As a result, it was revealed that biochemical indicators (ALT, AST, ALP, blood urea nitrogen, and creatinine) were increased and decreased hormonal parameters (FSH, LH, PG, and E2) in arsenic and 2,4-D and arsenic combination-treated groups. Moreover, increased lipid peroxidation (malondialdehyde level) and decreased antioxidant status (superoxide dismutase and catalase activities) were found in the co-exposure groups compared with the individual-exposure groups. Meanwhile, severe DNA damage was observed in co-exposure groups. Additionally, the levels of apoptotic (Bax, Caspase-3, Caspase-8, Caspase-9, p53, and PARP) and inflammation (NF kappa B, Cox-2, TNF-alpha, and TGF beta I) indexes in the co-exposure groups were markedly increased, whereas the levels of anti-apoptosis index (Bcl-2) were decreased. It was also observed that co-exposure with 2,4-D and arsenic caused more histopathological changes in tissues. Generally, these results show that co-exposure to 2,4-D and arsenic can seriously cause oxidative stress, DNA damage, apoptosis and inflammation while having toxicological risk for organisms. [GRAPHICS] .
Keywords: 2, 4-Dichlorophenoxyacetic; Arsenic; Dna Damage; Inflammation; Apoptosis; Rat